2008
DOI: 10.1111/j.1470-9856.2008.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Feminisation of Poverty’ in Costa Rica: To What Extent a Conundrum?

Abstract: Quantitative data from Costa Rica suggest that poverty is 'feminising', especially in respect of female-headed households, who, since the early 1990s, have constituted a progressively greater share of the population classifi ed as poor. This presents something of a conundrum given signifi cant attempts on the part of the state to promote gender equality and to direct public expenditure to low-income women. Some light on this apparent paradox is shed by qualitative fi eldwork undertaken in Guanacaste province w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…A plausible explanation of the decrease in births within marriage is that less women feel compelled to marry when they are pregnant after the law went into effect, since they are now able to obtain child support payments without marriage. This mechanism suggests that we might expect an increase in lone motherhood and a decrease in marriage rates, in line with the findings of Sylvia Chant (2009).…”
Section: Background and Data Descriptionsupporting
confidence: 84%
See 1 more Smart Citation
“…A plausible explanation of the decrease in births within marriage is that less women feel compelled to marry when they are pregnant after the law went into effect, since they are now able to obtain child support payments without marriage. This mechanism suggests that we might expect an increase in lone motherhood and a decrease in marriage rates, in line with the findings of Sylvia Chant (2009).…”
Section: Background and Data Descriptionsupporting
confidence: 84%
“…Of particular relevance to the present paper is the research presented in Sylvia Chant (2009). Chant argues that Costa Rica has indeed seen a "feminization of poverty", in the sense of a rising share of femaleheaded households among the poor.…”
Section: Introductionmentioning
confidence: 93%
“…Employment programmes implemented to alleviate some of the worst social impacts of the SAPs provided opportunities for women's empowerment and increased decision-making power and at the same time provoked conflicting and fractured feminine identities (Laurie 1999). More recently, some have suggested that there is an incipient crisis of the patriarchal family, with an increasing number of women refusing to accept patriarchal authority and expectations of traditional gender norms and behaviour (Chant 2009). New social movements brought increased visibility to social groups thus far marginalised, such as the lesbian, gay, bisexual and transgender community (Lind 2010).…”
Section: Migration Gender Relations and Motherhoodmentioning
confidence: 98%
“…En este caso se abordará la pobreza femenina valiéndose del ingreso como criterio para definirla y medirla, sin ignorar que diversos autores advierten acerca de las limitaciones de basarse únicamente en el ingreso y en otros aspectos mesurables para examinarla, y reconociendo la necesidad de incorporar enfoques que revelen la subjetividad de las mujeres y la multidimensionalidad de la pobreza (Chant, 2007(Chant, , 2009Moghadam, 1997). Algunos estudios cualitativos acerca de la manera en que las mujeres perciben la pobreza (Chant, 2009) demuestran que no necesariamente el punto más apremiante que resaltan es la falta de ingresos; para ellas una de las cuestiones más importantes es evadir la violencia y la pobreza secundaria a la que a veces son sometidas en los hogares encabezados por hombres.…”
Section: La Importancia Del Ingreso Y El Papel Del Mercado El Estadounclassified
“…Algunos estudios cualitativos acerca de la manera en que las mujeres perciben la pobreza (Chant, 2009) demuestran que no necesariamente el punto más apremiante que resaltan es la falta de ingresos; para ellas una de las cuestiones más importantes es evadir la violencia y la pobreza secundaria a la que a veces son sometidas en los hogares encabezados por hombres.…”
Section: La Importancia Del Ingreso Y El Papel Del Mercado El Estadounclassified